2015
DOI: 10.1007/s11244-015-0405-x
|View full text |Cite
|
Sign up to set email alerts
|

CO Dissociation at Vacancy Sites on Hägg Iron Carbide: Direct Versus Hydrogen-Assisted Routes Investigated with DFT

Abstract: The mechanism of activation of CO remains under debate in Fe-catalysed Fischer-Tropsch synthesis, in which iron carbides form under reaction conditions. Direct and H-assisted paths for CO activation and dissociation are investigated at carbon vacancy and non-vacancy sites on the Fe 5 C 2 (010) surface of Hägg iron carbide using density functional theory. The calculated overall energy barrier for direct and for H-assisted dissociation of CO via formation of an HCO intermediate is the same, 1.42 and 1.41 eV, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 77 publications
(149 reference statements)
1
35
1
Order By: Relevance
“…On the other hand, Petersen and Janse van Rensburg reported similar barriers for direct and H-assisted CO dissociation on this surface. 14 The main difference is their choice to remove the C atoms from the surface, rendering the surface more reactive for direct CO bond dissociation. Therefore, we also explored the CO dissociation in a vacancy site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Petersen and Janse van Rensburg reported similar barriers for direct and H-assisted CO dissociation on this surface. 14 The main difference is their choice to remove the C atoms from the surface, rendering the surface more reactive for direct CO bond dissociation. Therefore, we also explored the CO dissociation in a vacancy site.…”
Section: Resultsmentioning
confidence: 99%
“…Direct CO dissociation is more facile on the defective surface and shows an activation energy of 141 kJ/mol, in good agreement with the value found by Petersen and Janse van Rensburg. 14 Dissociation via the COH intermediate is also more facile, as the activation energy is lowered from 216 to 126 kJ/mol. The pathway via CHO remains nearly unaffected, as the CHO intermediate is slightly less stable in the vacancy as compared to the 2B 3 site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To fundamentally understand the initial process of FTS, it is very necessary and essential to study CO activation mechanisms on the surfaces of the catalysts. Theoretical research on CO adsorption and dissociation mechanisms on the Hägg carbide phase have attracted great attention. Huo et al studied the CO activation and surface carbon hydrogenation on Fe 5 C 2 (010), Fe 2 C­(011), Fe 3 C­(001), and Fe 4 C­(100) surfaces using Perdew–Burke–Ernzerhof (PBE) functional and found that direct CO cleavage can take place on the vacancy sites produced by CH 4 formation. The surface C-vacant sites also proved to be active for CO dissociation on the Fe 5 C 2 (010), Fe 5 C 2 (110) 0.00 , and Fe 5 C 2 (110) 0.80 surfaces by combining projector augmented wave (PAW)-RPBE and USPP-PW91 calculations. , Gracia et al studied CO hydrogenation using RPBE and found that with the surface carbon removed, the Fe 5 C 2 (100) facet shows high activity for both direct dissociation and CO hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the direct CO dissociation pathway corresponds to higher activity in comparison with the H-assisted CO dissociation [38] . Table 1 gives a comparison of the preferred pathways for the CO dissociation among different χ-Fe 5 C 2 surfaces [32,[39][40][41][42][43] . Obviously, the direct CO dissociation is the preferred CO activation pathway for the terrace-like χ- faces of χ-Fe 5 C 2 act as the active sites for the FTO.…”
Section: Introductionmentioning
confidence: 99%